Pengaruh Motivation dan Work Discipline terhadap Employee Performance (Studi Kasus pada Karyawan Pt. Mnc Sky Vision Sukabumi) - Ryan Kurniawan; Diky Aulia Akmal (Institut Manajemen Wiyata Indonesia, 2021)
The purpose of this study was to determine the effect of dimensions or variables, motivation and work discipline on employee performance. Methodology: The research method uses a survey method using a questionnaire distributed to 51 MNC Sky Vision employees. While the instrument quality testing techniques include validity, reliability and normality tests. And data analysis techniques using quantitative analysis, while for hypothesis testing using multiple linear regression analysis. Results: based on the results of the t test (partial) conducted that the motivation variable does not affect the performance of employees with a significance value above 0.05 (0.074 ≤ 0.05), while for work discipline variables affect the performance of employees with a significance value below 0, 05 (0.00 ≤ 0.05). Based on the F test (simultaneous) motivation and work discipline simultaneously have a positive effect on employee performance with a significance value below 0.05 (0.000 ≤ 0.05). But, in relation to the independent variable on the dependent variable, motivation and work discipline only have an effect of 42.3% on employee performance and 57.7% are influenced by variables not examined in this study. Limitations of the study: An analysis of the influence of motivation and work discipline is only done in one branch and only two dimensions or variables are tested. It is expected that the application of motivation can be formulated and adjusted to the existing working conditions in the company.